Schneehydrologische Untersuchungen am Pico de Teide (Teneriffa) - Becht, Michael (ERDKUNDE, 1991)
The snow ablation under conditions of sub-tropical high mountains was investigated at the Pico de Teide (28° 16'N, 16°38'W) during February and March 1990. The results are: (1) The snow density was extremely high at the beginning of the field observations and rose to the highest values over 700 kg/cbm during the ablation period. (2) The correlation of the snow density with the altitude above sea level is negative because the part of refreezing meltwater in the snow cover decreases with increasing altitude. (3) Snowmelt run-off, which occurs only in the lower parts, reaches 10-20% of the total ablation loss. Under the conditions of the intensive radiation in sub-tropical high mountains of Tenerife the ablation of the snow cover was dominated by high rates of evaporation and lower rates of sublimation. (4) Sometimes eolian sediments are transported with strong winds (> 100 km/h) and deposited on the snow cover. With the decrease of the albedo the ablation rate increases and reaches the highest values. (5) The movement of free water through the snow cover into the ground was obstructed by ice layers in the lower part of the snow cover and at the surface of the soil. (6) Due to a high rate of both evaporation and sublimation penitentes are built up episodically in regions over 2800 m a.s.l. during periods with cold air temperature.